2021
DOI: 10.3390/foods10123028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Peptidomics Analysis of Fermented Milk by Lactobacillus delbrueckii ssp. bulgaricus and Lactobacillus delbrueckii ssp. lactis

Abstract: Few studies have investigated the peptidomics of fermented milk by Lactobacillus delbrueckii. The aim of the present study was to interpret the peptidomic pattern of the fermented milk by five strains of L. delbrueckii ssp. bulgaricus and ssp. lactis prior to and after the simulated gastrointestinal digestion in vitro. The results indicated variations in the peptidomics among the samples, particularly between the samples of different subspecies. The peptides originating from β-casein were abundant in the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This high metabolic property enhances the fermentation ability of these strains with the production of essential metabolites (e.g., bioactive peptides, lactate, SCFA, and vitamins). These compound’s synthesis requires specific enzymes (e.g., proteinases and peptidases, glyceraldehyde-3-phosphate dehydrogenase, pyruvate kinase, phosphoketolase, acetate kinase, lactate dehydrogenase, riboflavin kinase, thiamine pyrophosphokinase, among others) of these strains, involved in proteolysis, and both phosphoketolase or Embden-Meyerhof (EMP) metabolic pathways ( Kandler, 1983 ; Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This high metabolic property enhances the fermentation ability of these strains with the production of essential metabolites (e.g., bioactive peptides, lactate, SCFA, and vitamins). These compound’s synthesis requires specific enzymes (e.g., proteinases and peptidases, glyceraldehyde-3-phosphate dehydrogenase, pyruvate kinase, phosphoketolase, acetate kinase, lactate dehydrogenase, riboflavin kinase, thiamine pyrophosphokinase, among others) of these strains, involved in proteolysis, and both phosphoketolase or Embden-Meyerhof (EMP) metabolic pathways ( Kandler, 1983 ; Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A method previously described [ 19 ] was followed with minor modification. Samples were analyzed using an EASY nLC 1200 system equipped with an Acclaim PepMapTM RSLC (50 μm × 15 cm, 2 μm, 100 Å).…”
Section: Methodsmentioning
confidence: 99%
“…Ye et al (2021) [ 4 ] reported the peptidomics of milk fermented by Lactobacillus delbrueckii both before and after the simulated gastrointestinal digestion. The peptides derived from β-casein were abundant in the samples of L. delbreuckii ssp.…”
mentioning
confidence: 99%